2021
DOI: 10.3892/etm.2021.9720
|View full text |Cite
|
Sign up to set email alerts
|

Poricoic acid A suppresses TGF‑β1‑induced renal fibrosis and proliferation via the PDGF‑C, Smad3 and MAPK pathways

Abstract: Renal interstitial fibrosis is the most important pathological process in chronic renal failure. Previous studies have shown that poricoic acid A (PAA), the main chemical constituent on the surface layer of the mushroom Poria cocos, has protective effects against oxidative stress and acute kidney injury. The present study aimed to investigate the potential roles of PAA on the pathological process of renal fibrosis and the associated molecular mechanism. The NRK-49F cell line was treated with transforming growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Transforming growth factor beta leads to mesangial activation, proliferation, and extracellular matrix production both directly via the TGFB/Smad pathway, and indirectly by stimulating PDGF and PDGFRB, which in turn activate the mesangial cells ( 18 , 19 ). Our data show an increase in TGFB coinciding with the aSMA upregulation on day 8 after IA LPS injection.…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factor beta leads to mesangial activation, proliferation, and extracellular matrix production both directly via the TGFB/Smad pathway, and indirectly by stimulating PDGF and PDGFRB, which in turn activate the mesangial cells ( 18 , 19 ). Our data show an increase in TGFB coinciding with the aSMA upregulation on day 8 after IA LPS injection.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence and development of renal fibrosis are a complex and dynamic process including inflammatory cell infiltration, fibroblast activation and proliferation, tubular atrophy, and microvascular degeneration 23 . A lot of genes have been reported to be involved in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated that TCM can be used to treat PF and other diseases [ 25 , 26 ]. For instance, a study has demonstrated that Poria cocos Wolf treatment inhibits TGF- β 1-stimulated renal fibroblast ECM accumulation, fibrosis formation as well as proliferation by suppressing the Smad3, PDGF-C, and MAPK pathway [ 27 ]. Furthermore, Zhou et al have proved that Taohe-Chengqi decoction extract exerts its antirenal fibrosis effect by regulating inflammatory, EMT process as well as ECM deposition [ 28 ].…”
Section: Discussionmentioning
confidence: 99%